A gold nanobipyramid-based photothermal reagent with functions of targeting and activatable fluorescence labeling for visual photothermal therapy. Issue 18 (3rd August 2022) - Wu, Xueke; Yan, Chenyuan; Mu, Lixuan; Wang, Yuan; She, Guangwei; Shi, Wensheng
Abstract : A gold nanobipyramid-based photothermal reagent with functions of targeting and activatable fluorescence labeling was constructed for visual photothermal therapy. Abstract : By assembling fluorophore-marked DNA stem-loops on the surface of gold nanobipyramids (AuNBPs) with an efficient photothermal conversion, we fabricated a multifunctional photothermal reagent (AuNBPs-mPEG/AA-TR). The sgc8 sequences that were embedded inside the DNA stem-loops can specifically target the PTK7, an overexpressed protein located on the surface of CCRF-CEM cells (human acute lymphoblastic leukemia T lymphocyte) to realize an active targeting function. Before the AuNBPs-mPEG/AA-TR bind to the PTK7 proteins, the DNA stem-loops are folded, and the fluorophore linked on the DNA stem-loop will be close to the AuNBPs. In this configuration, the fluorescence from the fluorophore is quenched by the AuNBPs. However, when the AuNBPs-mPEG/AA-TR bound to the PTK7 proteins through the sgc8 sequences, the DNA stem-loops can be opened partially to enable the fluorophore to be far away from the AuNBPs. As a result, the fluorescent signal will be activated. Therefore, the fluorescence can be used as a visual signal to reveal the binding between the AuNBPs-mPEG/AA-TR and CCRF-CEM cells (usually called activatable fluorescence labelling). While under irradiation of an 808 nm laser, the CCRF-CEM cells could be ablated through the photothermal therapy of the AuNBPs-mPEG/AA-TR with a high photothermal efficiency. Applying the AuNBPs-mPEG/AA-TR to Human B lymphoma cells (Ramos cells) and CCRF-CEM cells, we found that only the CCRF-CEM cells can be effectively targeted, actively fluorescently labeled, and readily ablated by the AuNBPs-mPEG/AA-TR. This work provides an alternative photothermal agent for the targeted therapy of tumors.